Current Activities to Implement Integrated Teaching Learning in Undergraduate Medical Education in Bangladesh: Students’ View (Bangladesh Journal of Medical Education, 2020)
The present study was conducted amongst students of all phases in eight medical colleges (4 govt. & 4 non-govt.) of Bangladesh to assess views of students about the current activities to implement integrated teaching learning in undergraduate medical education in Bangladesh. Among 956 students, 387(40.5%) were male and 569(59.5%) were female. This study revealed that 605(63.3%) students had participated in integrated teaching learning session, 328(54.3%) students disagreed that the subjects of different phases are arranged sequentially in curriculum and 265(43.8%) students responded that integrated sessions were conducted in large group sessions. More than half of the students (53.7%) stated that integrated teaching helped them to get better understanding of the topic and integrated teaching also helped them to improve application of knowledge. Insufficiency of infrastructure, allocated time, teachers’ training have been identified by respondents as barriers for implementing integrated teaching learning. Study recommended more awareness and training of teachers and students regarding integrated teaching learning. Study also recommended to choose contents which have much clinical importance for integrated teaching and which have been taught repeatedly in different departments.Bangladesh Journal of Medical Education Vol.11(1) 2020: 26-31